2011
DOI: 10.1186/1471-2407-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes increases and metformin reduces total, colorectal, liver and pancreatic cancer incidences in Taiwanese: a representative population prospective cohort study of 800,000 individuals

Abstract: BackgroundMetformin protection against cancer risk in Orientals is uncertain. We examined the possible metformin effect on total, esophageal, gastric, colorectal (CRC), hepatocellular (HCC) and pancreatic cancers in a Taiwanese cohort.MethodsA representative sample of 800,000 was drawn from the Taiwanese National Health Insurance data of 2000. A cohort of 480,984 participants 20 years or older, diabetes-cancer-free on 1st January 2000 was formed and categorized as four groups by DM and metformin usage status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
362
5
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(392 citation statements)
references
References 41 publications
16
362
5
9
Order By: Relevance
“…Finally, other factors like the different dosage of drugs may also result in the higher heterogeneity. For instance, in the study of Cardel et al (2014), the dose of the metformin use was approximately 450 DDD (defined daily dose) while it was 1000 DDD in the study of Lee et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, other factors like the different dosage of drugs may also result in the higher heterogeneity. For instance, in the study of Cardel et al (2014), the dose of the metformin use was approximately 450 DDD (defined daily dose) while it was 1000 DDD in the study of Lee et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows that eight cohort studies (Oliveria et al 2008;Currie et al 2009;Libby et al 2009;Lee et al 2011;Hsieh et al 2012;Ruiter et al 2012;Tsilidis et al 2014;Xu et al 2014) including 175,432 cases and 126,967 controls, and three case-control studies (Yang et al 2004;Bodmer et al 2012;Cardel et al 2014) including 3133 cases and 15,774 controls were retrieved in the meta-analysis. Two studies were based on American (Oliveria et al 2008;Xu et al 2014), seven studies were based on European (Yang et al 2004;Currie et al 2009;Libby et al 2009;Bodmer et al 2012;Ruiter et al 2012;Cardel et al 2014;Tsilidis et al 2014), and two studies were based on Chinese (Taiwan) (Lee et al 2011;Hsieh et al 2012). All the studies were published from 2004 to 2014.…”
Section: Publication Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin is a widely used anti-diabetic drug, which has been reported to exhibit potential anticancer activity (3). Previous studies have shown that metformin administration significantly reduces the incidence and mortality rates of various types of cancer, including gastric cancer (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous human cancers are reported to be associated with DM. Increased risk of carcinomas of liver (Lee et al, 2011), colon (Jin, 2008), pancreas (Ben et al, 2011), kidney (Joh et al, 2011), endometrium (Weiderpass et al, 1997), esophagus (Jiang et al, 2012) and thyroid (Aschebrook-Kilfoy et al, 2011) is seen among patients with DM. Studies investigating the association between DM and prostate cancer (PCa), however, have shown a controversial result, although most of the studies revealed that DM may be associated with a lowering of the risk for PCa.…”
Section: Introductionmentioning
confidence: 99%